An inductor-less step-up/step-down multilevel inverter with a single input source - Kei Eguchi; Akira Shibata; Wanglok Do; Yujiro Harada (Energy Reports, 2020)
This paper presents a step-up/step-down multilevel inverter with a single input source. To achieve inductor-less design, the proposed multilevel inverter is designed by switched-capacitor (SC) techniques. In the proposed inverter, the voltage of series-connected main capacitors is averaged by shifting the connection of flying capacitors alternately. At the same time, a multilevel output is generated by connecting some of the series-connected main capacitors to an output terminal via transfer switches. Unlike existing SC multilevel inverters with a single input source, the proposed SC multilevel inverter can provide small component counts, step-up/step-down conversion, and flexible conversion ratio. Concerning the proposed SC 5-level inverter, theoretical analysis, simulation program with integrated circuit emphasis (SPICE) simulations, and breadboard experiments are conducted to investigate the circuit characteristics. The results of these analysis demonstrate that 1. The proposed inverter can achieve step-down conversion as well as step-up conversion by converting a single input voltage; 2. The proposed inverter can reduce three circuit components from the series-parallel type inverter; and 3. When the output power is 200W, the proposed inverter can achieve about 83% and 93% efficiency in the step-up mode and the step-down mode respectively.
Keywords: 330; Full-bridge circuits; Inductor-less inverters; Multilevel inverters; Step-up/step-down inverters; Switched-capacitor techniques